Aménagement de l’acquisition: du trilinguisme fonctionnel à la pédagogie convergente - Alain Takam (International Journal of Evaluation and Research in Education (IJERE), 2013)
Social bilingualism, unlike official bilingualism, is very common. In most countries, the official language/s and tens or hundreds of other languages coexist; many such unofficial languages facing extinction. What is noticeable is that when language planning does not follow the ecological approach, i.e., when it emphasizes the strengthening of a particular language rather than the “structured diversity” of all the languages that make up a particular linguistic ecosystem, that can negatively impact the survival of minority languages. This study, which was carried out from the perspective of ecolinguistics, was aimed at promoting linguistic diversity through the protection of minority languages. It was essentially based on acquisition planning. The protection referred to here could be ensured, among other means, through the progressive acquisition of three or more languages in the education system. In Cameroon, a French – English bilingual country, the minority official language and many local languages are taught in school with varying degrees of success. It was interesting to critically look at some teaching approaches of those languages with the objective of showing how it could be possible, for those whose first language is neither French nor English, to better learn French and/or English, through convergent pedagogy, an educative approach based on the development of bilingualism or multilingualism.DOI: http://dx.doi.org/10.11591/ijere.v2i2.2021